Expanding the scope of substrate specificity for peptide asparaginyl ligases - Lim, Ching Koon (Nanyang Technological University, 2023)
Asparaginyl endopeptidases (AEPs) are Asn/Asp (Asx)-specific proteases. Peptide asparaginyl ligases (PALs) belong to AEPs that exhibit dominant ligase activity, making them valuable stand-alone biotechnological and biochemical tools for precision biomanufacturing of proteins. Structure-guided mutagenesis in AEP has been the gold standard for protein engineering, but it remains laborious and time-consuming. Meanwhile, AEP substrates are also an equally important parameter that affects ligation efficiency and often neglected, as their dipeptide leaving groups following AEP catalysis exist as competitive nucleophiles that reverse ligation reaction, thus requiring substantial amount of incoming labels to achieve desirable product yield, particularly in intermolecular ligation. My thesis showed that ligation product yield can be improved via alteration of substrate incoming (P1'' – P2'') and leaving groups (P1' – P2'). Besides, we have characterized lysine side chain-to-tail cyclization and showed its potential in multicyclic peptide drug design. Taken together, my thesis provides further insights into understanding the potential of peptide substrates, which serve as a vital subject for engineering to enhance ligation product yield in the development of biologics.